TECHNOLOGICAL CHAIN OF PROTECTION FOR THE COMPANY'S NETWORK INFRASTRUCTURE - Коробейнікова, Тетяна; Лужецька, Наталя; Кіщак, Марта (SWorldJournal, 2024)
This paper examines methods and tools for assessing network security risks, which constitute a variety of approaches and instruments aimed at identifying potential threats, vulnerabilities, and possible consequences for information systems and networks.